ANALISIS DAMPAK PP NO.109 TAHUN 2012 TERHADAP KINERJA PT. GUDANG GARAM, TBK DAN SOSIAL EKONOMI KOTA KEDIRI (STUDI KOMPARASI SEBELUM DAN SESUDAH DITERAPKANNYA PP NO. 109 TAHUN 2012) (Equilibrium: Jurnal Ekonomi Syariah, 2019)
This study aims to analyze the financial performance of PT. Gudang Garam, Tbk before and after the application of PP No. 109 of 2012 and analyze the socio-economic status of the city of Kediri before and after the application of PP No. 109 of 2012. The type of research used in this study is to use descriptive research methods with a qualitative approach. The results of this study indicate that the financial performance of PT. Gudang Garam, Tbk before the stipulation of PP No. 109/2012 as follows: The company is quite consistent in maintaining the rotation of its supply to generate profits from year to year. And it can be said that for 10 years, the company has experienced a steady increase in achieving a proportional level of sales. As for the financial performance of PT. Gudang Garam, Tbk after the enactment of PP No. 109/2012 as follows: For income, debt to equity ratio, profit before tax, net income, assets and equity tend to experience an increase. Socio-economic before the enactment of PP No. 109/2012 as follows: The population of the city of Kediri has increased. The rate of population growth is mainly driven by the factors of relative high birth rates and factors of population migration from outside the city to the City of Kediri because this region has a socio-economic appeal that is relatively better than the surrounding areas. While socio-economic after the enactment of PP No. 109/2012 as follows: In 2014 the city of Kediri ranked first in the highest unemployment in East Java. The reason is that in 2014 there were massive layoffs from PT. Gudang Garam. However, the positive impact of these layoffs is that employees who are laid off turn their professions into entrepreneurs in MSMEs. This condition makes the social economy of the city of Kediri more conducive.